Men, Masculinities, and Infertilities. - Allan, Jonathan A. (Masculinity, Sex and Popular Culture Series, 2022)
Drawing on diverse examples from literature, film, memoirs, and popular culture, Men, Masculinities, and Infertilities studies cultural representations of male infertility.